Condition assessment of power transformer on-load tap-changers using wavelet analysis. - Pengju Kang (IEEE Transactions on power delivery)
The operation of a power transformer on-load tap-changer (OLTC) produces a well-defined series of vibration bursts as its signature. Due to the harmonic and nonstationary nature of the transient vibration signal, traditional frequency and time-frequency techniques are on longer effective for characterization of this type of vibration signals, as the localized time domain features, such as delays between bursts, the number of bursts, and the strengths of bursts, are essential for the condition assessment of OLTC. A wavelet transform based technique is developed in this paper to characterize the OLTC vibration signals. This technique gives a simplified format for displaying and representing the essential features of the OLTC vibration signatures. Application results from a selector type OLTC demonstrate that the features extracted in the wavelet domain can be utilized to provide reliable indications of the actual heath of an OLTC